A Systematic Literature Review on the Role of Local Government in Cross-Sectoral Waste Management Integration in Jakarta, Indonesia - Rajanner Pangihutan Simarmata; Ficky Adi Kurniawan (Tecno Scientifica Publishing, 2026)
This article presented a systematic literature review (SLR) to examine the role of local government in the cross-sectoral integration of waste management in the Special Capital Region of Jakarta. Waste management in Jakarta evolved into a complex governance issue involving public services, environmental health, spatial planning, and aquatic pollution control. This study synthesized scientific publications and policy documents published over the previous ten years using a structured review approach. The findings revealed that local governments performed four main roles: regulatory, coordinative, service delivery, and supervisory/accountability. However, policy implementation remained predominantly oriented toward downstream treatment rather than source reduction. Key policy instruments identified included plastic restriction regulations, extended producer responsibility (EPR) schemes, community-based initiatives such as waste banks, and the development of waste processing infrastructure, including refuse-derived fuel (RDF) facilities. Major constraints included limited institutional capacity, weak inter-agency coordination, inconsistent enforcement, and low public compliance. The review highlighted that strengthening cross-sectoral integration required a strategic shift toward measurable source reduction, optimization of economic instruments and EPR mechanisms, integration of land-based waste management with marine litter prevention, and the development of data-driven monitoring systems to support sustainable metropolitan governance.